PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA TEMA PEDULI TERHADAP MAHLUK HIDUP KELAS IV SD - Nurfauziah, Nurfauziah; Dinda Yarshal (Jurnal Cakrawala Ilmiah, 2024)
This research aims to develop a Contextual Teaching and Learning-Based Student Worksheet that is suitable for use in the thematic learning process on the theme "Caring for Living Creatures" in class IV elementary school. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. However, in this study the ADDIE procedure was used only up to stage 3, namely the development stage. The instrument used to collect data was a validation questionnaire given to several expert validators, namely LKS expert validators, material expert validators and learning expert validators. The total score obtained from the LKS expert validation was 84.4, from the final validation of the material expert, namely 83.2 and from the learning expert it was 92.4. The average score from the experts' assessments is 86.6. From these scores it can be said that the CTL-based LKS with the theme "Caring for Living Creatures" which was developed is "Very Appropriate" for use in the thematic learning process for theme 3 "Caring for Living Creatures" in class IV elementary school